Analysis of Service Quality PT Pos Indonesia to Improve Market Share - Lalu Arman Mahadi; Harimukti Wandebori (UNIVED Press, 2024)
In Indonesia's postal and logistics business, PT Pos Indonesia faces increased competition. Despite logistics' annual growth, the company's market share has declined. To be competitive in the courier and logistics market, PT Pos Indonesia must design a business strategy to improve its service quality and complement its good operational performance. This requires recognizing customer priorities and improving the company's performance in these areas. PT Pos Indonesia can use Importance-Performance Analysis (IPA) to identify customer-important service quality dimensions and underperforming areas by conducting internal and external evaluations. This complete strategy will allow PT Pos Indonesia to prioritize its efforts, strategically allocate resources, and focus on service quality that will most effect customer satisfaction. Based on the investigation, integrated logistic cooperation and solutions were presented to fill service shortages. These efforts used integrated logistical partnerships, staff advocacy, and an advanced marketing platform to improve coordination and delivery speed, employee competencies, and consumer insights. These measures were meant to bridge the gap between customer expectations and service level agreements, delivery speed, personnel competence, and customer needs. These techniques can help PT Pos Indonesia boost customer satisfaction and market share.